p53-Mdm2 interaction targeted therapy by Nutlin-3 on nasopharyngeal carcinoma cells / Voon Yee Lin - Voon, Yee Lin (2016)
Nutlin-3, a small-molecule inhibitor of p53-Mdm2 interaction, is known to be effective against cancers expressing wild-type (wt) p53. p53 mutations are rare in nasopharyngeal carcinoma (NPC), and hence targeting the disruption of p53-Mdm2 interaction to reactivate p53 may offer a promising therapeutic strategy for NPC. This study hypothesized that reactivation of p53 in NPC cells may suppress NPC cell proliferation, and in addition, Nutlin-3 combined with cisplatin may further suppress the cancer cell proliferation more effectively. To investigate these possibilities, the effects of Nutlin-3 alone or in combination with cisplatin were tested on C666-1, an Epstein Barr virus (EBV)-positive NPC cell line bearing wt p53, in parallel with normal nasopharyngeal epithelial (NPE) NP69 and NP460 cells. Single drug treatment resulted in a concentration-dependent inhibitory effect on the cancer cell proliferation. Cisplatin was more cytotoxic to the NPE cells compared to the NPC cells, while Nutlin-3 was more effective and selective in inhibiting NPC cells. Cisplatin combined with Nutlin-3 showed stronger anti-proliferative effect against NPC cells and markedly suppressed its anchorage-independent growth on soft agar, suggesting that combined treatment was more effective than single drug therapy. Prior verification showed that C666-1, NP69 and NP460 cells retained the wt p53. Treatrnent with Nutlin-3 showed significant accumulation of p53, p2lWafl/Cipl and Mdm2 proteins in cells expressing wt p53 in comparison to p53-mutated cells. The effect of Nutlin-3 on the restoration of p53, p2lWafl/Cip1 and Mdm2 expression was impaired following p53-knocked down in NPC cells, and likewise the cells with p53 knockdown showed less sensitivity to Nutlin 3. These findings suggest that Nutlin-3 activates the p53 pathway and exerts its cytotoxicity on NPC cells in a pS3-dependent manner. The accumulation of Annexin V/Pl-stained cells showed treatment of NPC cells with cisplatin resulted in apoptosis and Nutlin-3-treated cells showed less percentage of apoptotic cells compared to the lll cisplatin-treated cells. Apoptosis, however, increased significantly in the cells teated with cisplatin and Nutlin-3. Similarly, Nutlin-3 positively upregulated BAX and PUMA protein expressions in NPC cells. The expression levels of these proteins also increased significantly in cells treated with cisplatin and Nutlin-3, concomitant with the detection of cleaved PARP level. Taken together, these findings suggest that Nutlin-3 sensitises NPC cells to cisplatin-induced apoptosis by modulating pro-apoptotic targets via the p53 pathway. In addition, an extended treatment period of NPC cells with Nutlin-3 did not result in the emergence of p53-mutated cells, albeit reduced sensitivity to Nutlin-3 was observed. This stresses on the importance of treabnent duration and clinical doses optimization to improve the efficacy of Nutlin-3 significantly. Therefore, the overall findings revealed supportive evidence of the effectiveness of combining cisplatin with Nutlin-3 as potential therapy against NPC.